Penerapan Media Video Tutorial pada Mata Pelajaran Teknologi Menjahit Kompetensi Penyelesaian Kampuh untuk Meningkatkan Hasil Belajar Siswa Kelas X Tata Busana SMK Negeri 3 Kediri - Sarah Merita Aristianti; Imami Arum Tri Rahayu; Peppy Mayasari; Deny Arifiana (Journal on Education, 2024)
This research is motivated by the fact that student learning outcomes of seam allowens competencies are still low. Students still not being able to absorb the lessons well because of limited learning media used. The aims of this research is : (1) to describe the implementation of video tutorial media of seam allowens competencies, (2) to describe the students responses to video tutorial media of seam allowens competencies, and (3) to describing student learning outcomes in seam allowens competencies. This type of research is Classroom Action Research (CAR). this research used quantitative data in the form of observations of learning implementation, student response data and student learning outcomes in the cognitive and psychomotor domains. The data collection methods used were observation sheets on learning implementation, student response questionnaires and student learning outcome tests. The results of this research are : (1) The results of the implementation of learning using the video tutorial media of seam allowens competencies obtained very good results with teacher observation results 90% and student observation results 93,1%, (2) The results of student responses regarding the application of video tutorial media of seam allowens competencies was very good with results 98,2% and (3) Student learning outcomes in the cognitive and psychomotor domains increased from cycle I to cycle III.